2016
DOI: 10.1111/head.12799
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Predictors of Post‐Injury Headache After Mild‐Moderate Traumatic Brain Injury in Veterans

Abstract: Rather than being a global risk factor, mild to moderate TBI was associated with poorer mental health outcomes, particularly for those who endorse headache. Findings underscore the possibility that Veterans with history of TBI who present with complaints of headache may represent a particularly vulnerable subgroup. Additionally, our findings suggest that clinical outcomes may be improved in those with neurotrauma by incorporating a focus on fatigue in treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 69 publications
(124 reference statements)
0
11
2
Order By: Relevance
“…Another characteristic shared by the two PPTH subgroups is high levels of PTSD when compared to headache-free TBI subjects, despite a similar incidence of moderate and severe TBI in these distinct groups. PTSD is a common characteristic among subjects with PPTH and is often reported to correlate with headache severity and disability (4749). A novel finding of the current study is that the interaction between PTSD level and the magnitude of the headache in the two PPTH subtypes followed opposite directions.…”
Section: Discussionmentioning
confidence: 99%
“…Another characteristic shared by the two PPTH subgroups is high levels of PTSD when compared to headache-free TBI subjects, despite a similar incidence of moderate and severe TBI in these distinct groups. PTSD is a common characteristic among subjects with PPTH and is often reported to correlate with headache severity and disability (4749). A novel finding of the current study is that the interaction between PTSD level and the magnitude of the headache in the two PPTH subtypes followed opposite directions.…”
Section: Discussionmentioning
confidence: 99%
“…This is compounded by limited preventative measures and lifestyle interventions received in a deployed setting [7]. History of concussion or mild TBI has been shown to correlate with poor mental health outcomes, particularly for those who endorse PTHA [811]. Furthermore, it is recognized that psychiatric symptoms can make recovery more difficult [12].…”
Section: Introductionmentioning
confidence: 99%
“…Relaxation training, counseling, cognitive behavioral therapy (CBT) and behavioral therapy have demonstrated efficacy in small controlled trials and retrospective case reports in treatment of post-traumatic headache disorders [8, 13, 14]. Two studies demonstrated significant improvement in headache outcomes, general well-being and up to 50% reduction in self-reported headache days with use of CBT or behavioral therapy [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety has also found to be linked to sleep disorders and fatigue. Sleep disorders, as well as fatigue, have been found to be predictors of PTH severity [57]. Cognitive impairment in PTH often presents with significant reductions in executive function, information processing speed, visual sensory input integration, and forgetfulness [58,59].…”
Section: Clinical Models and Overlapmentioning
confidence: 99%